PERFORMING IDENTITIES, SEXUALITIES AND PLEASURES: A TRIBUTE TO LEO BERSANI (1931-2022) - Maity, Abhijit (ShodhKosh: Journal of Visual and Performing Arts, 2022)
On 20 February 2022, Leo Bersani, who has been one of the leading philosophers, literary critics and intellectuals in gender and sexuality studies, passed away at the age of 90. In this essay, I shall draw attention to Leo Bersani’s theoretical oeuvre and attempt to offer a critical assessment of his major contributions to the field of LGBTIQ+ studies. The essay reveals that Bersani’s ideas concerning sexual identities, gender relations and somatic pleasures, and their relations with psyche, society, politics, families, and laws not only broaden the scope of understanding the complex phenomenon of human sexualities, but also underline the incomprehensibility of this phenomenon. This essay is divided into three small parts: Bersani’s life, works and death, his career as a literary critic, and his queer activism in literary and political circle. The essay also details Bersani’s intellectual journey, critical insights, and political engagements, defending human inclination towards pleasure and sexual freedom against the backdrop of socio-political tensions which emerged during the height of AIDS epidemic in America.